Lithium oxide solid electrolyte material and preparation method and application thereof
By doping multiple elements in the Ta and P positions of LiTa2PO8, the concentration of lithium ions and vacancy is regulated, and the safety hazards of organic electrolytes in lithium-ion batteries and the problem of low ion conductivity of oxide electrolytes in room temperature is solved, and lithium oxides are realized The high ionic conductivity and electrochemical stability of solid electrolytes meet the needs of commercial applications.
Patent Information
- Application Number
- CN202411541179.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
The organic electrolyte used in existing lithium-ion batteries is easy to decompose under high temperature or overcharging, which poses safety risks. The room temperature ionic conductivity of oxide electrolytes such as LiTa2PO8 is low and cannot meet the requirements of commercial large-scale applications.
By doping a variety of specific metal elements and Si elements in the Ta and P positions of LiTa2PO8, the concentration of lithium ions and vacancy is regulated, the migration barrier of lithium ions is reduced, and the ionic conductivity of lithium oxide solid electrolyte is improved.
It significantly improves the ionic conductivity of lithium oxide solid electrolytes, enhances the electrochemical stability and safety of the material, and meets the requirements of commercial applications.
Smart Images

Figure CN119230925A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a lithium oxide solid electrolyte material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become a widely-watched secondary battery due to their high energy density, excellent cycle stability, and no memory effect. After decades of development, lithium-ion batteries have been industrialized and are the main energy supply components for new energy vehicles and some electronic products. However, the organic electrolyte used in traditional lithium-ion batteries is prone to decomposition under high temperature or overcharge conditions; and the organic electrolyte has a low ignition point, which can easily cause the battery to catch fire or explode, posing a huge safety hazard.
[0003] Compared with organic electrolytes, inorganic solid electrolytes have higher thermal stability and wider electrochemical window. Using inorganic solid electrolytes instead of flammable organic electrolytes is beneficial to improve battery safety. In addition, inorganic solid electrolytes can also match high-voltage positive electrodes and metal lithium negative electrodes to improve the energy density of batteries. Inorganic solid electrolytes can be divided into oxide electrolytes, sulfide electrolytes and halide electrolytes according to their composition. Among them, sulfide and halide electrolytes are difficult to commercialize due to their poor stability in wet air and high cost. Li in oxide electrolytes 6.4 LqCy 1.4 Ta 0.6 O 12 (LLZTO) has high ionic conductivity and excellent electrochemical stability, making it one of the most promising commercial oxide solid electrolytes. However, LLZTO easily reacts with H2O and CO2 in the air to form an insulating layer of LiOH and Li2CO3, which reduces the ionic conductivity of the material [Adv. Funct. Mater. 2022, 33(3), 2209120]; and the generated Li2CO3 has poor wettability with metallic lithium, and is prone to form a large interface resistance when matched with a metallic lithium negative electrode.
[0004] The novel oxide solid electrolyte LiTa2PO8 (LTPO) has an extremely high theoretical ionic conductivity (~35 mS / cm) [J. Phys. Chem. C 2019, 123(32), 19282 - 19287], and it does not chemically react with H2O and CO2, possessing excellent air stability. However, the room-temperature ionic conductivity of currently prepared LTPO is relatively low (0.1 - 0.4 mS / cm) [ACS Appl. Energy Mater. 2023, 6(9), 4810 - 4816; Ceram. Int. 2023, 49(6), 8718 - 8724; Mater. Sci. 2020, 56(3), 2425 - 2434], which cannot meet the requirements of large-scale commercial applications. Element doping can regulate the lithium-ion concentration in the lattice and effectively improve the room-temperature ionic conductivity of LTPO. For example, doping Si element at the P site [Chem. Mater, 2021, 33(17): 6909 - 6917], doping Zr element at the Ta site, etc. [Adv. Mater. 2023, 35(40), e2303730]. However, the improvement effect of doping LTPO with a single element on its ionic conductivity is limited, and other doping methods are urgently needed.
[0005] Co-doping with multiple elements can not only inherit the advantages of single-element doping, but also the co-doped elements may form a synergistic effect to further improve the material properties. Based on this strategy, by directionally incorporating different elements into the Ta site and P site of the LTPO solid electrolyte, synergistically regulating the lithium-ion and vacancy concentrations in the lattice, it is expected to significantly improve the ionic conductivity of the material. Summary of the Invention
[0006] The purpose of the present invention is to provide a lithium oxide solid electrolyte material, its preparation method and application, by overcoming the deficiencies of the prior art.
[0007] To achieve the above purpose, the technical solutions adopted by the present invention are as follows:
[0008] In the first aspect, the present invention provides a lithium oxide solid electrolyte material, and the chemical general formula of this lithium oxide solid electrolyte material is: Li x Ta 2-m-n A m B n P 1-q Si q O8;
[0009] Among them, 0 < m ≤ 0.6, 0 ≤ n < 2, 0 < q ≤ 0.4, and 0.1 < m + n ≤ 2;
[0010] A is a +3-valent element, selected from at least one of Ga, In, Sc, Y, Ho, Er, Tm, Yb, Lu;
[0011] B is an element different from A, and is selected from at least one of Ti, Zr, Hf, Nb, Mo, W, Sn, and Sb;
[0012] When B is a +4 valent element and is selected from at least one of Ti, Zr, Hf, and Sn, x=1+2m+n+q;
[0013] When B is a +5 valence element and is selected from at least one of Nb and Sb, x=1+2m+q;
[0014] When B is a +6 valent element and is selected from at least one of Mo and W, x=1+2m-n+q.
[0015] The present invention adopts Si element to dope the P position of LiTa2PO8, selects specific A element and B element to dope the Ta position of LiTa2PO8, and controls the Si / P ratio and the doping amounts of A and B elements, so as to achieve the regulation of lithium ion and vacancy concentrations in the lithium oxide solid electrolyte material, reduce the migration barrier of lithium ions, and thus improve the ionic conductivity of the lithium oxide solid electrolyte material.
[0016] In addition, the above Li x Ta 2-m-n A m B n P 1-q Si q The x, m, n and q in O8 satisfy the principle of electrical neutrality in terms of numerical values; element B is different from element A in that the type and / or valence of element B is different from element A.
[0017] Optionally, the above Li x Ta 2-m-n A m B n P 1-q Si q Specifically, x in O8 may be 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, preferably 1.4 to 1.9, more preferably 1.5 to 1.8;
[0018] m can specifically be 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, preferably 0.05 to 0.3, more preferably 0.1 to 0.25;
[0019] n can specifically be 0.01, 0.1, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.5, 1.7, 1.9, preferably 0.05 to 0.8, more preferably 0.1 to 0.6;
[0020] Specifically, q may be 0.01, 0.03, 0.1, 0.15, 0.2, 0.25, 0.3, or 0.4, preferably 0.05 to 0.3, and more preferably 0.1 to 0.2.
[0021] As a preferred embodiment of the lithium oxide solid electrolyte material of the present invention, A is at least one of Ga, Y, and Yb, and B is at least one of Zr, Nb, and Mo.
[0022] In a second aspect, the present invention provides a method for preparing the above-mentioned lithium oxide solid electrolyte material, which comprises the following steps:
[0023] S1. Press Li x Ta 2-m-n A m B n P 1-q Si q The stoichiometric ratio of each element in O8 is obtained by mixing lithium source, tantalum source, A source, B source, silicon source and phosphorus source, and performing ball milling and pre-sintering in sequence to obtain a solid electrolyte precursor;
[0024] S2, performing secondary ball milling on the solid electrolyte precursor in S1 to obtain a solid electrolyte precursor with refined particles;
[0025] S3, cold pressing the solid electrolyte precursor after the particles in S2 are refined into sheets and sintering at high temperature in sequence to obtain a lithium oxide solid electrolyte material.
[0026] Optionally, the lithium source is selected from at least one of lithium oxides, lithium hydroxides, lithium carbonates, lithium acetates, and lithium organic salts; the tantalum source is selected from at least one of tantalum oxides, tantalum hydroxides, tantalum carbonates, tantalum acetates, and tantalum organic salts; the A or B source is selected from at least one of oxides containing A or B, hydroxides containing A or B, carbonates containing A or B, acetates containing A or B, and organic salts containing A or B.
[0027] As a preferred embodiment of the method for preparing the lithium oxide solid electrolyte material of the present invention, the lithium source in step S1 is lithium carbonate (Li2CO3), the tantalum source is tantalum pentoxide (Ta2O5), the silicon source is at least one of silicon dioxide and organic silicon, and the phosphorus source is at least one of phosphorus pentoxide, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.
[0028] As a preferred embodiment of the method for preparing the lithium oxide solid electrolyte material of the present invention, the pre-sintering temperature in step S1 is 720-1000° C. and the time is 0.5-20 h.
[0029] Pre-sintering under the above conditions can better promote the decomposition of the raw materials (Li2CO3, NH4H2PO4) and prevent them from generating a large amount of gas during the high-temperature sintering process in the subsequent step S3, thereby preparing a high-density lithium oxide electrolyte ceramic sheet.
[0030] As a preferred embodiment of the method for preparing the lithium oxide solid electrolyte material of the present invention, the high temperature sintering in step S3 is performed at a temperature of 900 to 1200° C. and a time of 0.1 to 20 h.
[0031] The high-temperature sintering process mainly includes phase generation and grain growth processes. The sintering temperature and time will affect the physical phase and grain size of the material.
[0032] As a preferred embodiment of the method for preparing the lithium oxide solid electrolyte material of the present invention, the rotation speed of the first ball milling in step S1 is 200-800 rpm, and the time is 0.5-24 h; and / or the rotation speed of the second ball milling in step S2 is 200-800 rpm, and the time is 0.5-24 h.
[0033] The primary ball milling in step S1 is mainly used to reduce the particle size of the raw materials and to mix the raw materials uniformly, and the secondary ball milling in step S2 is mainly used to reduce the particle size range of the electrolyte precursor (200nm to 20μm). Specifically, the medium for the primary ball milling or the secondary ball milling can be zirconia microspheres with a diameter of 2mm to 10mm.
[0034] In a third aspect, the present invention provides application of the above lithium oxide solid electrolyte material in a secondary battery.
[0035] Specifically, the application of lithium oxide solid electrolyte materials in secondary batteries means that the lithium oxide solid electrolyte materials can be used alone as inorganic solid electrolytes, or can be used alone or together with other inorganic solid electrolyte materials as conductive fillers for polymer solid electrolytes.
[0036] In a fourth aspect, the present invention provides an all-solid-state lithium-ion battery, which includes a positive electrode, a solid electrolyte and a negative electrode, wherein the solid electrolyte is prepared using the above-mentioned lithium oxide solid electrolyte material.
[0037] As a preferred embodiment of the all-solid-state lithium-ion battery of the present invention, the negative electrode is metallic lithium, and an interface buffer layer is provided between the solid electrolyte and the negative electrode; the interface buffer layer is selected from at least one of a lithium ion polymer electrolyte film, a fluoride coating, a nitride coating, a sulfide coating, and an oxychloride coating. The positive electrode material in the positive electrode is selected from one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium manganese oxide, and lithium-rich manganese-based materials.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] The present invention achieves the goal of regulating the concentration of lithium ions and vacancies in the lithium oxide solid electrolyte material, reducing the migration barrier of lithium ions, and thereby effectively improving the ionic conductivity of the lithium oxide solid electrolyte by simultaneously doping a variety of specific metal elements at the Ta position of LiTa2PO8 and doping Si at the P position, and controlling the doping amounts of the metal elements and Si elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The scanning electron microscope images of the lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 3 and 7;
[0041] Figure 2 X-ray diffraction spectra of the lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 1 to 3;
[0042] Figure 3 The impedance test diagram of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 1 to 3;
[0043] Figure 4 X-ray diffraction spectra of lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 4 and 5;
[0044] Figure 5 The impedance test diagram of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 4 and 5;
[0045] Figure 6 X-ray diffraction spectra of lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 6 to 11;
[0046] Figure 7 The impedance test diagram of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 6 to 11;
[0047] Figure 8 X-ray diffraction spectra of lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 12 and 13;
[0048] Fig. 9 The impedance test diagram of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 12 and 13;
[0049] Fig.10 X-ray diffraction spectra of the lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 14 and 15;
[0050] Fig.11 The impedance test diagram of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 14 and 15;
[0051] Fig.12 X-ray diffraction pattern of the lithium oxide solid electrolyte material in Examples 7, 16, 17, 18, and 19;
[0052] Fig.13 Impedance test chart of the lithium oxide solid electrolyte material in Examples 7, 16, 17, 18, and 19;
[0053] Fig.14 X-ray diffraction pattern of the lithium oxide solid electrolyte material in Comparative Examples 1-7;
[0054] Fig.15 Impedance test chart of the lithium oxide solid electrolyte material in Comparative Examples 1-7;
[0055] Fig.16 Charge and discharge cycle performance chart of the lithium oxide solid electrolyte material in Comparative Example 1 and Example 7. Detailed implementation manners
[0056] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0057] Other materials, reagents, etc. used in the examples can be obtained from commercial sources without special instructions.
[0058] Li x Ta 2-m-n A m B n P 1-q Si q O8
[0059] 0 < m ≤ 0.6, 0 ≤ n < 2, 0 < q ≤ 0.4, and 0.1 < m + n ≤ 2;
[0060] A is a +3-valent element, selected from at least one of Ga, In, Sc, Y, Ho, Er, Tm, Yb, and Lu;
[0061] B is an element different from A, selected from at least one of Ti, Zr, Hf, Nb, Mo, W, Sn, and Sb;
[0062] Wherein, when B is a +4-valent element, selected from at least one of Ti, Zr, Hf, and Sn, then x = 1 + 2m + n + q;
[0063] Wherein, when B is a +5-valent element, selected from at least one of Nb, Sb, and Bi, then x = 1 + 2m + q;
[0064] Wherein, when B is a +6-valent element, selected from at least one of Mo and W, then x = 1 + 2m - n + q.
[0065] Table 1 x, m, n, q, A and B of lithium oxide solid electrolyte materials in Examples 1 to 19
[0066]
[0067]
[0068] Table 2 x, m, n, q, A and B of lithium oxide solid electrolyte materials in Comparative Examples 1 to 7
[0069] x m n q A B Comparative Example 1 1 0 0 0 / / Comparative Example 2 1.4 0.2 0 0 Y / Comparative Example 3 1.2 0 0 0.2 / / Comparative Example 4 1.2 0.05 0 0.1 Y / Comparative Example 5 1.3 0.1 0 0.1 Y / Comparative Example 6 1.8 0.2 0 0.4 Y / Comparative Example 7 1.8 0.2 0.2 0.2 Y Zr
[0070] Example 1
[0071] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.5 Ta 1.8 Y 0.2 P 0.9 Si 0.1 O8 (denoted as Y,Si-LTPO-1).
[0072] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0073] S1. According to Li 1.5 Ta 1.8 Y 0.2 P 0.9 Si 0.1 The stoichiometric ratio of each element in O8 is measured, Li2CO3, Ta2O5, Y2O3, SiO2 and NH4H2PO4 (wherein the Li element is 10% in excess), and then 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm are added, and the mixture is evenly mixed at 400 rpm for 10 hours, and then the evenly mixed slurry is placed in an 80°C blast oven and dried for 12 hours, and then transferred to a muffle furnace and pre-sintered at 800°C for 20 hours to obtain a pre-sintered solid electrolyte precursor;
[0074] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0075] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0076] Example 2
[0077] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.7 Ta 1.7 Y 0.3 P 0.9 Si 0.1 O8 (denoted as Y,Si-LTPO-2).
[0078] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that in Embodiment 1.
[0079] Example 3
[0080] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.6 Ta 1.8 Y 0.2 P 0.8 Si 0.2 O8 (denoted as Y,Si-LTPO-3).
[0081] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that in Embodiment 1.
[0082] Example 4
[0083] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.6 Ta 1.8 Ga 0.2 P 0.8 Si 0.2 O8 (denoted as Ga,Si-LTPO-1).
[0084] The method for preparing the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 1, except that Y2O3 in step S1 is replaced by Ga2O3.
[0085] Example 5
[0086] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.6 Ta 1.8 Yb 0.2 P 0.8 Si 0.2 O8 (denoted as Yb,Si-LTPO-1).
[0087] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 1, except that Y2O3 in step S1 is replaced by Yb2O3.
[0088] Example 6
[0089] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.7 Ta 1.7 Y 0.2 Zr 0.1 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-1).
[0090] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0091] S1. According to Li 1.7 Ta 1.7 Y 0.2 Zr 0.1 P 0.8 Si 0.2 The stoichiometric ratio of each element in O8 is measured, Li2CO3, Ta2O5, ZrO2, Y2O3, SiO2 and NH4H2PO4 (wherein the Li element is 10% in excess), and then 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm are added, and the mixture is ball-milled at 400 rpm for 10 hours to be uniformly mixed, and then the uniformly mixed slurry is placed in an 80°C blast oven to dry for 12 hours, and then transferred to a muffle furnace and pre-sintered at 800°C for 20 hours to obtain a pre-sintered solid electrolyte precursor;
[0092] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0093] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0094] Example 7
[0095] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-2).
[0096] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that of Example 6.
[0097] Example 8
[0098] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 2.6 Ta 1.2 Y 0.6 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-3).
[0099] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that of Example 6.
[0100] Example 9
[0101] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 2.6 Ta 0.8 Y 0.2 Zr 1.0 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-4).
[0102] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that of Example 6.
[0103] Example 10
[0104] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 3.4 Y 0.2 Zr 1.8 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-5).
[0105] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that of Example 6.
[0106] Embodiment 11
[0107] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 2.0 Ta 1.6 Y 0.2 Zr 0.2 P 0.6 Si0.4 O8 (denoted as Y, Zr, Si-LTPO-6).
[0108] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is the same as that of Example 6.
[0109] Example 12
[0110] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Yb 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Yb, Zr, Si-LTPO-1).
[0111] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that Y2O3 is replaced by Yb2O3 in step S1.
[0112] Example 13
[0113] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Ga 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Ga, Zr, Si-LTPO-1).
[0114] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that Y2O3 is replaced by Ga2O3 in step S1.
[0115] Embodiment 14
[0116] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.6 Ta 1.6 Y 0.2 Nb 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Nb, Si-LTPO-1).
[0117] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that in step S1, ZrO2 is replaced by Nb2O5.
[0118] Embodiment 15
[0119] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.4 Ta 1.6 Y 0.2 Mo 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Mo, Si-LTPO-1).
[0120] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that ZrO2 is replaced by MoO3 in step S1.
[0121] Example 16
[0122] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-7).
[0123] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that the sintering temperature is adjusted to 1050° C. in step S3.
[0124] Embodiment 17
[0125] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-8).
[0126] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that the sintering temperature is adjusted to 1150° C. in step S3.
[0127] Embodiment 18
[0128] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-9).
[0129] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that the sintering time in step S3 is adjusted to 2 hours.
[0130] Embodiment 19
[0131] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-10).
[0132] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is basically the same as that in Embodiment 6, except that the sintering time in step S3 is adjusted to 4 hours.
[0133] Comparative Example 1
[0134] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is LiTa2PO8 (recorded as LTPO-Comparative Example-1).
[0135] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0136] S1. According to the stoichiometric ratio of each element in LiTa2PO8, weigh Li2CO3, Ta2O5 and NH4H2PO4 (wherein the Li element is 10% in excess), add 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm, and mix them evenly at 400 rpm for 10 hours. Then, place the mixed slurry in an 80°C blast oven and dry it for 12 hours, then transfer it to a muffle furnace and pre-sinter it at 800°C for 20 hours to obtain a pre-sintered solid electrolyte precursor;
[0137] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0138] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0139] Comparative Example 2
[0140] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is Li 1.4 Ta 1.8 Y 0.2 PO8 (denoted as Y-LTPO-Comparative Example-2).
[0141] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0142] S1. According to Li 1.4 Ta 1.8 Y 0.2 The stoichiometric ratio of each element in PO8 is as follows: Li2CO3, Ta2O5, Y2O3 and NH4H2PO4 (wherein the Li element is 10% in excess) are weighed, and then 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm are added, and the mixture is ball-milled at 400 rpm for 10 hours to be uniformly mixed, and then the uniformly mixed slurry is placed in an 80°C blast oven to dry for 12 hours, and then transferred to a muffle furnace and pre-sintered at 800°C for 20 hours to obtain a pre-sintered solid electrolyte precursor;
[0143] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0144] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0145] Comparative Example 3
[0146] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is Li 1.2 Ta2P 0.8 Si 0.2 O8 (referred to as Si-LTPO-Comparative Example-3).
[0147] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0148] S1. According to Li 1.2 Ta2P 0.8 Si 0.2 The stoichiometric ratio of each element in O8 is measured, Li2CO3, Ta2O5, SiO2 and NH4H2PO4 (wherein the Li element is 10% in excess), and then 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm are added, and the mixture is evenly mixed at 400 rpm for 10 hours, and then the evenly mixed slurry is placed in an 80°C blast oven and dried for 12 hours, and then transferred to a muffle furnace and pre-sintered at 800°C for 20 hours to obtain a pre-sintered solid electrolyte precursor;
[0149] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0150] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0151] Comparative Example 4
[0152] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is Li 1.2 Ta 1.9 Y 0.05 P 0.9 Si 0.1 O8 (denoted as Y, Si-LTPO-Comparative Example-4).
[0153] The preparation method of the lithium oxide solid electrolyte material in this comparative example is the same as that in Example 1.
[0154] Comparative Example 5
[0155] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is Li 1.3 Ta 1.9 Y 0.1 P 0.9 Si 0.1 O8 (denoted as Y, Si-LTPO-Comparative Example-5).
[0156] The preparation method of the lithium oxide solid electrolyte material in this comparative example is the same as that in Example 1.
[0157] Comparative Example 6
[0158] A comparative example of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this comparative example is Li 1.8 Ta 1.8 Y 0.2 P 0.6 Si 0.4 O8 (denoted as Y, Si-Comparative Example-6).
[0159] The preparation method of the lithium oxide solid electrolyte material in this comparative example is the same as that in Example 1.
[0160] Comparative Example 7
[0161] An embodiment of the lithium oxide solid electrolyte material of the present invention, the chemical formula of the lithium oxide solid electrolyte material in this embodiment is Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 O8 (denoted as Y, Zr, Si-LTPO-7).
[0162] The preparation method of the lithium oxide solid electrolyte material described in this embodiment is:
[0163] S1. According to Li 1.8 Ta 1.6 Y 0.2 Zr 0.2 P 0.8 Si 0.2 The stoichiometric ratio of each element in O8 is measured, Li2CO3, Ta2O5, Y2O3, SiO2, ZrO2 and NH4H2PO4 (wherein the Li element is 10% excess), and then 5 times the total mass of isopropanol and 10 times the total mass of zirconium oxide microspheres with a diameter of 2 to 10 mm are added, and the mixture is ball-milled at 400 rpm for 10 hours to be uniformly mixed, and then the uniformly mixed slurry is placed in an 80°C forced air oven and dried for 12 hours to obtain a solid electrolyte precursor;
[0164] S2, placing the solid electrolyte precursor in a ball mill, adding zirconia microspheres with a diameter of 2 to 10 mm in an amount 10 times the mass of the solid electrolyte precursor, and ball milling at 250 rpm for 10 hours to obtain a submicron solid electrolyte precursor powder;
[0165] S3. 500 mg of submicron solid electrolyte precursor powder was pressed in a mold with a diameter of 13 mm at a pressure of 10 MPa for 2 min. After demolding, it was transferred to a muffle furnace and sintered at a high temperature of 1100°C for 3 h. After cooling, a lithium oxide solid electrolyte ceramic sheet was obtained.
[0166] Performance Testing
[0167] 1. Scanning electron microscope test (SEM)
[0168] Figure 1 The scanning electron microscope images of the lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 3 and 7 are shown. Figure 1 As shown in a, there are a lot of pores between the grains of LiTa2PO8 solid electrolyte, and the density is low, which is not conducive to the rapid migration of lithium ions. Si is doped at the P position of LiTa2PO8, and Y is doped at the Ta position or Y and Zr are doped at the same time ( Figure 1 b~c), which can effectively reduce the pores between grains. In particular, doping Y and Zr elements at the Ta position of LiTa2PO8 can significantly improve the density of lithium oxide solid electrolyte materials.
[0169] 2. X-ray diffraction test (XRD)
[0170] Figure 2 is the X-ray diffraction spectrum of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 1 to 3, Figure 4 is the X-ray diffraction spectrum of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 4 and 5, Figure 6 is the X-ray diffraction spectrum of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 6 to 11, Figure 8 is the X-ray diffraction spectrum of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 12 and 13, Fig.10 1 and 15 are X-ray diffraction spectra of the lithium oxide solid electrolyte materials in Comparative Example 1 and Examples 14 and 15. Figure 2 , Figure 4 , Figure 6 , Figure 8 and Fig.10 As shown, elements are doped at the P and Ta positions of LiTa2PO8 at the same time, and the resulting lithium oxide solid electrolyte materials have the same diffraction peaks as the LiTa2PO8 solid electrolyte, indicating that the lithium oxide solid electrolytes doped with different elements have the same physical phase.
[0171] Fig.12 Shown are X-ray diffraction spectra of lithium oxide solid electrolyte materials prepared under different secondary sintering conditions (Examples 7, 16, 17, 18, and 19), indicating that adjusting the secondary sintering temperature and sintering time within a certain range will not affect the physical phase of the lithium oxide solid electrolyte material.
[0172] Fig.14X-ray diffraction spectra of lithium oxide solid electrolyte materials in Comparative Examples 1 to 7. The lithium oxide solid electrolyte materials obtained by doping and modifying only at the P position or Ta position of LiTa2PO8, or at both the P position and Ta position of LiTa2PO8, all have the same diffraction peaks as the LiTa2PO8 solid electrolyte. Y, Zr, Si-LTPO-Comparative Example-7 shows different diffraction peaks from LTPO-Comparative Example-1, indicating that the pre-sintering step affects the physical phase of the lithium oxide solid electrolyte material.
[0173] 3. Impedance test (EIS)
[0174] Test method: A uniform layer of gold single-element conductor was coated on the surface of the lithium oxide solid electrolyte ceramic sheet in each embodiment and comparative example by ion sputtering, and then placed between two stainless steel discs with a thickness of 0.5 mm, and connected to a Biologic electrochemical workstation, and an AC impedance spectrum test was performed at 25°C, and the test frequency range was 1 Hz to 7 MHz.
[0175] Figure 3 It is the impedance spectrum of the lithium oxide solid electrolyte material in comparative example 1 and embodiments 1 to 3; among them, the internal resistance of LTPO-comparative example-1 is 658Ω, the internal resistance of Y,Si-LTPO-1 is 120Ω, the internal resistance of Y,Si-LTPO-2 is 141Ω, and the internal resistance of Y,Si-LTPO-3 is 98Ω; it shows that doping Y element at the Ta position of LiTa2PO8 and doping Si element at the P position of LiTa2PO8 can significantly reduce its internal resistance and improve ionic conductivity.
[0176] Figure 5 It is the impedance spectrum of the lithium oxide solid electrolyte material in comparative example 1 and embodiments 4 and 5; among them, the internal resistance of LTPO-comparative example-1 is 658Ω, the internal resistance of Yb,Si-LTPO-1 is 154Ω, and the internal resistance of Ga,Si-LTPO-1 is 135Ω; it shows that in addition to the Y element, the use of other +3 valent metal elements (Ga, Yb) to dope at the Ta position of LiTa2PO8 can significantly improve its ionic conductivity.
[0177] Figure 7It is the impedance spectrum of the lithium oxide solid electrolyte material in Comparative Example 1 and Examples 6 to 11; wherein, the internal resistance of LTPO-Comparative Example-1 is 658Ω, the internal resistance of Y,Zr,Si-LTPO-1 is 74Ω, the internal resistance of Y,Zr,Si-LTPO-2 is 59Ω, the internal resistance of Y,Zr,Si-LTPO-3 is 91Ω, the internal resistance of Y,Zr,Si-LTPO-4 is 86Ω, the internal resistance of Y,Zr,Si-LTPO-5 is 124Ω, and the internal resistance of Y,Zr,Si-LTPO-6 is 107Ω; indicating that simultaneously doping Y and Zr elements at the Ta position of LiTa2PO8 and simultaneously doping Si element at the P position of LiTa2PO8 can significantly reduce its internal resistance and improve ionic conductivity.
[0178] Fig. 9 It is the impedance spectrum of the lithium oxide solid electrolyte material in comparative example 1 and embodiments 12 and 13; among them, the internal resistance of LTPO-comparative example-1 is 658Ω, the internal resistance of Yb, Zr, Si-LTPO-1 is 104Ω, and the internal resistance of Ga, Zr, Si-LTPO-1 is 100Ω; it shows that in addition to the co-doping of Y and Zr elements, the use of other +3 valent metal elements (Ga or Yb) and Zr elements for simultaneous doping modification at the Ta position of LiTa2PO8 can significantly improve its ionic conductivity.
[0179] Fig.11 It is the impedance spectrum of the lithium oxide solid electrolyte material in comparative example 1 and embodiments 14 to 15; among them, the internal resistance of LTPO-comparative example-1 is 658Ω, the internal resistance of Y, Nb, Si-LTPO-1 is 98Ω, and the internal resistance of Y, Mo, Si-LTPO-1 is 120Ω; it shows that in addition to the co-doping of Y and Zr elements, the use of other valence metal elements (Nb, Mo) and Y element for simultaneous doping modification at the Ta position of LiTa2PO8 can significantly improve its ionic conductivity.
[0180] Fig.13 The impedance spectra of the lithium oxide solid electrolyte materials in Examples 7, 16, 17, 18 and 19; wherein the internal resistance of Y, Zr, Si-LTPO-2 is 59Ω, the internal resistance of Y, Zr, Si-LTPO-7 is 71Ω, the internal resistance of Y, Zr, Si-LTPO-8 is 67Ω, the internal resistance of Y, Zr, Si-LTPO-9 is 75Ω, and the internal resistance of Y, Zr, Si-LTPO-10 is 117Ω; indicating that the secondary sintering time and sintering temperature have a greater influence on the conductivity of the examples of lithium oxide solid electrolyte materials, wherein the preferred sintering time and sintering temperature are 1100°C and 3h.
[0181] Fig.15The impedance spectrum of the lithium oxide solid electrolyte material in Examples 1 to 7; wherein, the internal resistance of LTPO-Comparative Example-1 is 658Ω, the internal resistance of Y-LTPO-Comparative Example-2 is 269Ω, the internal resistance of Si-LTPO-Comparative Example-3 is 160Ω, the internal resistance of Y,Si-LTPO-Comparative Example-4 is 272Ω, the internal resistance of Y,Si-LTPO-Comparative Example-5 is 234Ω, the internal resistance of Y,Si-LTPO-Comparative Example-6 is 226Ω, and the internal resistance of Y,Zr,Si-LTPO-Comparative Example-7 is 6941Ω. Compared with LiTa2PO8, single element doping (S element doping) at the P position of LiTa2PO8 or single element doping (Y element doping) at the Ta position can improve the ionic conductivity of the lithium oxide solid electrolyte to a certain extent, but the improvement effect is significantly inferior to the dual doping modification of specific elements at the Ta and P positions of LiTa2PO8. Combined with the internal resistance of the lithium oxide solid electrolyte material in Examples 1 to 3, it is shown that the ionic conductivity of Y and Zr co-doped LiTa2PO8 is affected by the concentration of the doping element. The ionic conductivity of Y and Zr co-doped LiTa2PO8 first increases with the increase of the concentration of the doping element. When the concentration of the doping element reaches a certain level, the ionic conductivity of the material decreases with the further increase of the concentration of the doping element. Comparing the impedance values of Y, Zr, Si-LTPO-Comparative Example-7 and Y, Zr, Si-LTPO-2, it is shown that the pre-burning step greatly affects the internal resistance of the lithium oxide solid electrolyte material.
[0182] 4. Calculation of ionic conductivity
[0183] The ionic conductivity of lithium oxide solid electrolyte materials is calculated by the following formula:
[0184] Ionic conductivity = L / (S*R)
[0185] Where L is the thickness of the solid electrolyte sheet (cm), S is the area of the solid electrolyte sheet (cm 2 ), R is the internal resistance of the solid electrolyte sheet (Ω) measured by the Biologic electrochemical workstation.
[0186] Table 3 Ionic conductivity of lithium oxide solid electrolyte materials in various embodiments and comparative examples
[0187]
[0188] As shown in Table 3, the ionic conductivity of the lithium oxide solid electrolyte materials in Examples 1 to 19 all reached 0.65 mS / cm, indicating that the lithium oxide solid electrolyte material of the present invention has excellent ionic conductivity.
[0189] According to the ionic conductivity of Comparative Examples 1 to 3, Y element doping (single element doping) at the Ta position of LiTa2PO8 can increase the ionic conductivity of LiTa2PO8 from 0.16 mS / cm to 0.37 mS / cm; Si element doping (single element doping) at the P position of LiTa2PO8 can increase the ionic conductivity of LiTa2PO8 from 0.16 mS / cm to 0.62 mS / cm; This indicates that single element doping modification of LiTa2PO8 with Y element or Si element can slightly improve the ionic conductivity.
[0190] According to the ionic conductivity of Comparative Examples 4 to 6 and Examples 6 to 11, the ionic conductivity of LiTa2PO8 is affected by the interaction of the doping elements at the Ta and P positions, and the influence mechanism is complex, not a simple superposition of the effects of single-element doping (Y element doping or Si element doping). Only when the doping amount of multiple doping elements is controlled within a suitable range can different doping elements form synergistic silencing when regulating the concentration of lithium ions and vacancies, significantly improving the ionic conductivity of lithium oxide solid electrolyte materials.
[0191] In addition, it can be seen from Comparative Example 7 that the pre-firing step greatly affects the ionic conductivity of the lithium oxide solid electrolyte material.
[0192] 5. Charge and discharge cycle test
[0193] (1) The positive electrode sheet is composed of an aluminum foil and an electrode material layer coated on the surface of the aluminum foil, wherein the electrode material layer is lithium nickel cobalt manganese oxide LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), binder polyvinylidene fluoride (PVDF) and conductive agent vapor grown carbon fiber (VGCF) are composed in a mass ratio of 8:1:1;
[0194] (2) The negative electrode is made of metallic lithium;
[0195] (3) The lithium oxide / negative electrode interface buffer layer is selected as a PEO@LiTFSI polymer layer (average thickness is 30 μm), wherein the PEO@LiTFSI polymer layer is composed of polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) with a molar ratio of EO:Li=10:1.
[0196] The lithium oxide solid electrolyte materials in Example 7 and Comparative Example 1 were respectively used as solid electrolytes, and assembled into button batteries with the above-mentioned positive electrode sheet, negative electrode sheet, interface buffer layer and other accessories, and packaged under a pressure of 50 MPa; then, the batteries were subjected to charge and discharge tests at room temperature (25°C) and 1C current density. The test results are as follows: Fig.16 shown.
[0197] Among them, capacity retention rate = discharge capacity after cycle / first cycle discharge capacity*100%.
[0198] according to Fig.16 It can be seen that the battery assembled with the lithium oxide solid electrolyte material in Example 7 has an initial discharge capacity of 150.75 mAh g -1 The capacity retention rate after 250 cycles of charge and discharge is 90.8%. The capacity retention rate of the batteries assembled with the lithium oxide solid electrolyte materials in Examples 3 to 5 and 12 to 15 after 250 cycles is more than 85%. The initial discharge capacity (150.50 mAh g -1 ) is close to the initial discharge specific capacity of the battery assembled with the solid electrolyte material provided in Example 7. However, with the increase in the number of cycles, the battery discharge specific capacity decreases rapidly, and the capacity retention rate after 250 cycles is only 76.4%. The above shows that the solid-state battery assembled with the lithium oxide solid electrolyte material provided by the present invention has excellent cycle stability.
[0199] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium oxide solid electrolyte material, characterized in that: The general chemical formula of the lithium oxide solid electrolyte material is: Li x Ta 2-m-n A m B n P 1-q Si q O8; Among them, 0 < m ≤ 0.6, 0 ≤ n < 2, 0 < q ≤ 0.4, and 0.1 < m + n ≤ 2; A is an element with a valence of +3, selected from at least one of Ga, In, Sc, Y, Ho, Er, Tm, Yb, Lu; B is an element different from A, selected from at least one of Ti, Zr, Hf, Nb, Mo, W, Sn, Sb; When B is an element with a valence of +4 and selected from at least one of Ti, Zr, Hf, Sn, x = 1 + 2m + n + q; When B is an element with a valence of +5 and selected from at least one of Nb, Sb, x = 1 + 2m + q; When B is an element with a valence of +6 and selected from at least one of Mo, W, x = 1 + 2m - n + q.
2. The lithium oxide solid electrolyte material according to claim 1, characterized in that A is at least one of Ga, Y, Yb, and B is at least one of Zr, Nb, Mo.
3. The method for preparing the lithium oxide solid electrolyte material according to any one of claims 1 to 2, characterized in that: It includes the following steps: S1. Press Li x Ta 2-m-n A m B n P 1-q Si q The stoichiometric ratio of each element in O8 is obtained by mixing lithium source, tantalum source, A source, B source, silicon source and phosphorus source, and performing ball milling and pre-sintering in sequence to obtain a solid electrolyte precursor; S2. Secondarily ball-mill the solid electrolyte precursor in S1 to obtain a solid electrolyte precursor with refined particles; S3. Sequentially cold-press the solid electrolyte precursor with refined particles in S2 into a sheet and perform high-temperature sintering to obtain a lithium oxide solid electrolyte ceramic sheet.
4. The method for preparing the lithium oxide solid electrolyte material according to claim 3, characterized in that: In step S1, the temperature of the pre-sintering is 720 - 1000 °C, and the time is 0.5 - 20 h.
5. The method for preparing the lithium oxide solid electrolyte material according to claim 3, characterized in that: In step S3, the temperature of the high-temperature sintering is 900 - 1200 °C, and the time is 0.1 - 20 h.
6. The method for preparing the lithium oxide solid electrolyte material according to claim 3, characterized in that: In step S1, the rotation speed of the primary ball-milling is 200 - 800 rpm, and the time is 0.5 - 24 h; And / or in step S2, the rotation speed of the secondary ball-milling is 200 - 800 rpm, and the time is 0.5 - 24 h.
7. Application of the lithium oxide solid electrolyte material according to any one of claims 1 - 2 in a secondary battery.
8. An all-solid-state lithium-ion battery, comprising a positive electrode, a solid electrolyte and a negative electrode, characterized in that: The solid electrolyte is prepared from the lithium oxide solid electrolyte material according to any one of claims 1 - 2.
9. The all-solid-state lithium-ion battery according to claim 8, characterized in that: The negative electrode is metallic lithium, and an interface buffer layer is provided between the solid electrolyte and the negative electrode; The interface buffer layer is selected from at least one of a lithium-ion polymer electrolyte film, a fluoride coating, a nitride coating, a sulfide coating, and an oxychloride coating.
Citation Information
Patent Citations
Method for improving solid-state battery interface stability by polymer electrolyte
CN110233285A
Solid electrolyte material, solid electrolyte, method for producing same, and all-solid-state battery
CN115699212A
Intervus bar, pack housing including it, bettery pack including it, and method manufacturing the same
KR1020250136513A
Solid ion conductor, solid electrolyte including the same, electrochemical device including the same, and preparation method thereof
US20220044837A1
Solid electrolyte material for lithium secondary battery, electrode, and battery
US20220216507A1
